Diagnostic criteria for corticobasal syndrome: a comparative study. Issue 4 (21st October 2011) - Mathew, Robert; Bak, Thomas H; Hodges, John R
Abstract : Introduction: There are no well-established criteria for patients with corticobasal syndrome. The authors have attempted to clarify this area by comparing and applying three sets of well-known criteria (from Toronto, the Mayo Clinic and Cambridge). Patient and methods: The authors first compared the three criteria for overlap and differences, and then applied them to a group of 40 consecutive patients (22 men, mean age 67 years) with focal cortical syndrome characterised by apraxia and Parkinsonism, at both the early stages and later in their illness. Results: Despite an overall similarity, there were major differences in the criteria which affect their applicability. Cognitive impairment was ubiquitous even at presentation, with speech and language impairment the commonest feature. Some classic features, alien limb and myoclonus, were present in a minority only even late in their course. The three criteria were equally applicable to patients with advanced disease (Toronto 92.5%, Cambridge 90% and Mayo 87.5%). Thirty patients (75%) satisfied all three criteria. Using this group as a 'gold standard', 73.3% fulfilled the Cambridge criteria at presentation compared with 46.7% and 36.7% for the Toronto and Mayo Clinic criteria, respectively. Concordance between criteria was poor. Conclusion: Cognitive impairment, especially language impairment, was prominent from onset of disease. The Cambridge criteria apply to a higher proportion of cases at an early stage of corticobasal syndrome. The authors suggest a minor modification to capture the high prevalence of aphasia.